Meninjau Kembali Pemikiran Nurcholish Madjid: Neo-Republikanisme Islam dan Kewargaan Demokratis di Indonesia - Bunta, Abd. Firman; Hasmawati; Djumat, Irwan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
The rise of conservatism and identity polarization underscores the urgency of constructing religious discourse compatible with inclusive democracy. Nurcholish Madjid's thought offers a synthesis of Islamic moral principles and modern democratic values. This study employs qualitative library research with a hermeneutic content-analysis approach, drawing primarily on Nurcholish's works and relevant secondary literature. The findings reveal that his framework constitutes an Islamic neo-republicanism characterized by freedom as non-domination, civic participation, deliberation, and public ethics. Unlike many neo-modernist Muslim intellectuals who remain at the level of normative pluralism, Nurcholish advances a more substantive conception of political freedom. At the core of his thought lies the rejection of all forms of domination - whether symbolic or through religious formalism - and the insistence that both state and religion must secure inclusive spaces that guarantee equality for all citizens. This study concludes that Nurcholish Madjid's Islamic neo-republicanism is not merely a reinterpretation of pluralism, but rather a paradigm of democratic citizenship grounded in progressive Islamic ethics, offering a substantive conceptual framework for strengthening democratic life in Indonesia.